A new subspecies of the subterranean beetle Speoplanes biocovensis Müller, 1934 (Coleoptera: Leiodidae: Cholevinae: Leptodirini) from Bosnia and Herzegovina: the first occurrence of the genus outside Croatia - Vrbica, Maja; Vesović, Nikola; Rađa, Tonći; Ćurčić, Srećko (Zootaxa, 2024)
A new subterranean leptodirine leiodid beetle, Speoplanes biocovensis bosnicus Vrbica, Vesović, Rađa & Ćurčić, ssp. n., is described and diagnosed from a pit in southern Bosnia and Herzegovina. This is the first discovery of the genus Speoplanes Müller, 1911 in this country and the first discovery outside Croatia. Important morphological features of the new taxon are presented, including aspects of the male and female genitalia. The subspecies is endemic to the Dinaric mountain range of Bosnia and Herzegovina. A key to the identification of taxa of the genus Speoplanes is added.